PROFILE OF BRONCHIAL ASTHMA PATIENTS AT A PULMONARY OUTPATIENT CLINIC OF A TERTIARY HOSPITAL IN INDONESIA - Naura Alya Hirmadiani; Alfian Nur Rosyid; Budi Utomo (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights: Budesonide-Formoterol was the most commonly prescribed medication for controlling and relieving symptoms in most individuals with bronchial asthma. Most patients reported good control of their asthma, and most also reported no subjective problems. Abstract Background: Bronchial asthma is a common disease affecting the patient's quality of life and impacting daily life. The incidence of asthma is increasing in many countries around the world, although hospitalization and death rates due to asthma have decreased. Objective: This study aimed to explain the sociodemographic (age, sex, body mass index, smoking status) and clinical (comorbidities, subjective complaints, asthma control status, pharmacological therapy, and pharmaceutical step therapy) characteristics of bronchial asthma patients at the Pulmonary Outpatient Clinic the Universitas Airlangga Hospital, Surabaya, Indonesia. Material and Method: An analytic observational study with retrospective cross-sectional research was conducted from December 2021 to January 2023 using secondary data in medical records with total sampling as the sampling technique. Result: From 70 cases, 35 patients made the three-times visits. The majority of these patients who met the inclusion criteria were female (78.6%), 50 to 59 years old (27.1%), had class 1 obese (38.6%), non-smokers (77.1%), and had no comorbidities (28.6%). On the first, second, and third visits, the patients had no subjective complaints, had well-maintained asthma status control, used controllers and relievers in the form of Budesonide-Formoterol, and did not receive additional therapy. They had step therapy in the category of preferred controllers and relievers, steps 1–2. Conclusion: The majority of bronchial asthma patients at Universitas Airlangga Hospital, Surabaya, Indonesia, were female, aged 50–59 years, non-smokers, obese class 1, had no subjective complaints, well-controlled asthma, preferred controllers and relievers steps 1–2, using Budesonide-Formoterol as controller and reliever therapy, and did not receive additional therapy.